Photochemical approaches to azetidines - Baldwin, Kipp (2022)
This thesis concerns the application of continuous flow photochemistry to the 4 electrocyclisation of nitrogen-containing heterocycles, in particular 2-pyridinones and 1,2-dihydropyridines, for the synthesis of so-called Dewar heterocycles, which were envisaged as convenient starting materials for the synthesis of sp3-rich, highly substituted small molecules.